IMPLEMENTING RAPID NEEDS ASSESSMENT TO IMPROVE HUMANITARIAN AID DISTRIBUTION FOLLOWING THE 2025 FLASH FLOOD IN PADANG CITY, INDONESIA: A COMMUNITY SERVICE EXPERIENCE - Ade Teti Vani; Irwan Triansyah; Nadia Purnama Dewi; Dessy Abdullah; Yuri Haiga; Debie Anggraini; Prima Adelin; Dita Hasni (Nusantara Hasana Journal, 2026)
Humanitarian aid is one of the most critical components of disaster response. However, relief distribution during the emergency phase is frequently driven by donor availability rather than by the actual needs of affected communities. Consequently, while essential supplies such as food and drinking water are often adequately provided, personal necessities that directly influence dignity, hygiene, and daily living remain insufficient. Rapid Needs Assessment (RNA) is recommended as a systematic approach to identify priority needs and improve the effectiveness of humanitarian interventions. This community service program aimed to implement a Rapid Needs Assessment before humanitarian aid distribution for victims of the 2025 flash flood in Padang City, Indonesia. The program was conducted during the emergency response period following the flash flood on 26 November 2025. A collaborative team of university lecturers and members of the Indonesian Medical Association (IDI) Padang Branch conducted field observations and semi-structured interviews with affected households at evacuation sites. Information on assistance already received and unmet priority needs was collected and used to guide the procurement and distribution of relief items. Most affected households had already received temporary shelter, food, and clean water. However, essential personal items—including towels, baby supplies, underwear, blankets, prayer equipment, umbrellas, and raincoats—remained insufficient. Implementing Rapid Needs Assessment enabled the humanitarian team to provide targeted assistance, complement existing relief efforts, minimize duplication, and address overlooked needs. Rapid Needs Assessment improved the relevance and effectiveness of humanitarian aid distribution. Collaboration between higher education institutions and professional organizations offers a practical model for evidence-based community service in disaster response.